Variants of uncertain clinical significance in hereditary breast and ovarian cancer genes: best practices in functional analysis for clinical annotation - Monteiro, Alvaro N; Bouwman, Peter; Kousholt, Arne N; Eccles, Diana M; Millot, Gael A; Masson, Jean-Yves; Schmidt, Marjanka K; Sharan, Shyam K; Scully, Ralph; Wiesmüller, Lisa; Couch, Fergus; Vreeswijk, Maaike P G (Journal of medical genetics, 2020)
Correspondence to Dr Alvaro N Monteiro, Cancer Epidemiology, H. Lee Moffitt Cancer Center and Research Institute, Tampa, FL 33612, USA; Alvaro.Monteiro@Moffitt.org ; Dr Maaike P G Vreeswijk, Human Genetics, Leiden University Medical Center, Leiden, 2300RC, The Netherlands; M.P.G.Vreeswijk@lumc.nl Introduction Since the identification and cloning of BRCA1 in 1994,1 and shortly thereafter of BRCA2,2 genetic tests of germline DNA to identify pathogenic variants in genes linked to hereditary breast and ovarian cancer (HBOC) have become mainstream.3 These tests are critical to identify women at increased risk relative to the general population. In ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/), a clinically oriented database, currently ~37% of BRCA1 and ~45% of BRCA2 unique variants recorded are VUS. [...]there is a critical need to classify variants according to their pathogenicity.Table 1 Fraction of VUS in BRCA1 and BRCA2 Databases BIC* ClinVar† BRCA Exchange‡ gnomAD§ N % (%VUS) N % (%VUS) N % (%VUS) N % BRCA1 unique variants 1781 100 5821 100 7898 100 2936 100 BRCA1 VUS 891 50.0 (100) 2146 36.9 (100) 5186 65.7 (100) n/a n/a BRCA1 missense 607 34.1 (68.1) 1715 29.5 (79.9) 1892 24.0 (36.5) 938 31.9 BRCA1 missense VUS 569 31.9 (63.9) 1633 28.1 (76.1) 1714 21.7 (33.1) n/a n/a BRCA2 unique variants 2000 100 8119 100 10 422 100 4262 100 BRCA2 VUS 1065 53.3 (100) 3615 44.5 (100) 6980 67.0 (100) n/a n/a BRCA2 missense 891 44.6 (83.7) 3111 38.3 (86.1) 3484 33.4 (49.9) 1909 44.8 BRCA2 missense VUS 838 41.9 (78.7) 3011 37.1 (83.3) 3190 30.6 (45.7) n/a n/a *BIC (https://research.nhgri.nih.gov/bic/) is a locus-specific database established in 1995 for BRCA1 and BRCA2 variants, including loci primarily found in clinical or research testing. †ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/) is a public archive of reports of the relationships among human variations and phenotypes and includes submissions reporting variants found in patient samples from clinical or research testing, and from the literature (note: [...]developers of functional assays should consider that clinical recommendations are unlikely to be made based on variants in genes for which the association has not been robustly established. [...]a detailed understanding of the strength of evidence for association between each gene (and its variant alleles) and HBOC risk should be sought to evaluate the clinical utility of a proposed functional assay. Missense variation is unlikely to significantly affect the overall protein function when located in disordered regions or in repeat motifs. [...]functional assays for these regions (or for a protein with a large portion of its coding sequence composed by these regions) may not be a priority.